Systematic Review and Pooled Analysis of the Impact of Treatment-Induced Lymphopenia on Survival of Glioblastoma Patients - Saeed, A.; Bentzen, S.M.; Mishra, M.V. (International journal of radiation oncology, biology, physics, 2021)
Lymphopenia is a known toxicity of chemotherapy and radiation therapy (RT), part of the standard treatment for glioblastoma (GBM). Given the immune system's role in cancer control and general health, a number of single-institution studies have examined the association between treatment-related lymphopenia and survival outcomes of GBM patients. We performed a systematic review and pooled analysis to evaluate the association between lymphopenia and overall survival (OS) for GBM patients undergoing chemoRT. Following PRISMA guidelines, a systematic review of the MEDLINE database and abstracts from ASTRO, ASCO, and SNO annual meetings was conducted. Inclusion criteria included: (1) retrospective/prospective studies of human subjects (2) GBM patients (3) treated with chemoRT (4) reported lymphopenia and OS outcomes (5) analyzed lymphopenia and OS association. Analysis was conducted using inverse variance-weighted random effects to generate a pooled estimate of the hazard ratio of association between lymphopenia and OS. 104 studies were identified, with 11 studies meeting the inclusion criteria, representing 2,196 unique patients. The threshold of lymphopenia varied between studies (lymphocyte count cutoff value range of 400 - 1200 cells/uL; mode 500 cell/uL). The time of lymphopenia onset was dichotomized into two groups (time-point vs time-range), with 6 studies tabulating the incidence of lymphopenia defined at a fixed time point approximately 2-months after the start of RT, while 5 studies utilized a time-range, tabulating the incidence of lymphopenia defined as any occurrence of lymphopenia from the start of RT to approximately 2-months after the start of RT. The mean overall pooled incidence of lymphopenia for all 11 studies was 32.4%, and was 21.1% vs 41% for time-point studies and time-range studies, respectively. Lymphopenia was associated with increased risk of death, with a pooled HR of 1.78 (95% CI: 1.46 – 2.17, P < 0.00001) for the time-point studies, and a pooled HR of 1.38 (95% CI: 1.24 – 1.55, P < 0.00001) for the time-point studies. There was no significant heterogeneity between studies (P = 0.6 for time-point and P = 0.5 for time-range studies). Available pooled analysis of MVA estimates of HR for the time-range studies were confirmatory, with pooled HR of 1.36 (95% CI: 1.12 – 1.65, P < 0.002), with significant heterogeneity between studies, P = 0.02. These results strengthen observations from previous individual single-institution studies and better defines the magnitude of the association between treatment-related lymphopenia with decreased OS in GBM patients, highlighting lymphopenia as a poor prognostic factor. These results are hypothesis generating, stimulating a better understanding regarding causality and underscores the need for investigations into strategies to mitigate lymphopenia. Such insights may improve outcomes and possibly shed light on the limited efficacy of immunotherapy for the treatment of GBM. A. Saeed: None. S.M. Bentzen: Travel Expenses; University of Copenhagen. M.V. Mishra: Employee; Orthofix. Research Grant; ASTRO, Keep Punching. Advisory Board; Patient Centers Outcomes Research Institute (PCORI. Travel Expenses; Patient Centers Outcomes Research Institute (PCORI.